NAVIGATING MANDATORY BIODIESEL POLICY: A QUALITATIVE ANALYSIS OF THE DYNAMICS OF CATALYST RESEARCH, FEEDSTOCK DIVERSIFICATION, AND INDUSTRY RESPONSES IN INDONESIA'S ENERGY TRANSITION - Cut Rahmah Saputri; Jalaluddin; M. Yusuf (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study analyzes the implementation of the mandatory biodiesel policy in Indonesia, focusing on the dynamics of catalyst research, feedstock diversification, and industry responses in the context of the national energy transition. The mandatory policy, which began with B10 in 2016 and increased to B35 in 2023, aims to reduce dependence on fossil fuels by utilizing the potential of palm oil as the world's largest producer. Using a qualitative approach with a case study design, the research was conducted in four provinces: West Java, East Java, North Sumatra, and Riau over eight months, involving 35 informants from researchers, policymakers, and industry players. Data were collected through in-depth interviews, field observations, and documentation studies, analyzed using thematic analysis methods. The results show that biodiesel catalyst research has made significant progress in utilizing local materials such as rice husk ash and eggshells, but faces a large gap between laboratory success and industrial implementation due to minimal collaboration and funding for applied research. Feedstock diversification is still hampered by the dominance of palm oil, which reaches 95 percent, while alternatives such as castor oil, animal fats, and microalgae are not yet economically competitive. The industry's response to the mandatory policy is polarized, with large, vertically integrated companies able to adapt through technology investment and capacity expansion, while small and medium-sized producers face structural constraints such as limited capital, access to raw materials, and weak bargaining power. The misalignment between ambitious policy targets, limited technological readiness, and uneven industrial capacity creates an implementation gap that hinders the achievement of a sustainable energy transition. The study recommends establishing a research-industry collaboration platform, strengthening feedstock diversification policies, empowering small and medium-sized producers, conducting public education campaigns, and cross-ministerial coordination through a dedicated energy transition agency to develop a realistic and coordinated long-term roadmap.